A Psychoanalytic Examination of Female Trafficking Depicted in Rashel Lloyd's Girls Like Us: Insights from Sigmund Freud's Theoretical Framework - Hayder Ali Abdul Hasan and Fazel Asadi Amjad (Journal of Daoist Studies, 2026)
The present study aimed to examine the phenomenon of female trafficking from a psychoanalytic perspective using Sigmund Freud's theoretical framework. The psychological analysis of the book Girls Like Us by Rachel Lloyd was conducted with the aim of discovering the hidden psychological layers of victims of sex trafficking; the focus was on how the painful and traumatic experiences of the victims penetrated their unconscious structure and were reflected in their behaviors and psychological reactions. In this research, the fundamental concepts of Freud's theory, including repression, displacement, id, ego, and superego, were relied on to examine the psychological dimensions of this phenomenon from deeper angles. To collect data, a qualitative content analysis method was chosen and the texts of the book were studied and coded. Information was extracted from the memories, quotes, and narratives expressed by survivors of female trafficking in the text of the book. Each of these data was examined from a psychoanalytic perspective, and an attempt was made to identify signs of the functioning of psychological defense mechanisms among the statements and experiences of these girls. Psychoanalytic concepts such as the suppression of memories of sexual abuse, the conflict between the id and the superego, and the representation of repressed anxieties in sudden behaviors were analyzed. The data were coded and interpreted by several researchers to prevent the influence of individual bias and bias and to increase the validity of the analysis. As a result, it was determined that female trafficking has consequences beyond physical harm and has caused disruption in their psychological and identity structure. Analysis of the narratives in the book showed that many victims resorted to mechanisms such as repression, denial, and identification to survive in difficult circumstances; bitter memories of the past were repressed at the unconscious level of their minds and resurfaced in the form of constant anxieties, nightmares, and risky behaviors. In many cases, the conflict between the demands of the institution and the moral limitations of the superego led to anxiety and psychological disintegration in the victims.